Pengaruh Pelatihan Kepemimpinan Transformasional Kepala Ruangan terhadap Implementasi Komunikasi Efektif oleh Perawat Pelaksana - Pandie, Fance Roynaldo; Riti, Irlin Falde (Universitas Faletehan, 2023)
One of the main causes of patient safety problems is the non-optimal implementation of effective communication SOPs by nurses. Whereas, the room head as a first line manager has an important role in implementing effective communication through a transformational leadership style. This study aimed to analyze the influence of transformational leadership training for room heads on the implementation of effective communication by nurses. This research used a pre-experimental design with a one group pretest post-test design approach. The sample size in the study was 197 nurses who were selected by a non-probability sampling technique, namely convenience sampling. A questionnaire consisting of 20 questions was used to measure nurses' perceptions of transformational leadership style in implementing effective communication. The test used in this research used the Wilcoxon test. The Wilcoxon test results showed a significant difference in the implementation of effective communication before and after transformational leadership training (p value <0.001). There is an influence of transformational leadership training for room heads on the implementation of effective communication by nurses. Transformational leadership style can be applied to minimize errors in the implementation of effective communication SOP.